Some considerations on the construction of Public Art Networks - Grandas, Carme (CAP - Cadernos de Arte Pública / Public Art Journal, 2020)
Although it has not been until recent times that the concept of Public Art exists, it was formerly born as an ornamental presence in gardens and streets and squares. Today, Public Art includes any artistic language and materials, playing a role not only in the renewal or the development of urban public spaces, but also an important role of remembrance and identity.